Analisis Daya Saing Pengembangan Lembaga Pendidikan Di SDI Al-Huda Kota Kediri - Khafidhotun Nasikhah; Agus Zaenul Fitri (Institut Agama Islam Tribakti Kediri, 2022)
This study aims to determine the management strategy used in the development of SDI Al Huda, Kediri City. Al Huda can experience fairly rapid development in the last 2 periods by implementing total quality management. This is based on the strength of the team work to carry out continuous renewal by improving the quality of service both from the internal and external side of the institution. This is evidenced by the fact that in the last 2 periods, Al Huda has been increasing the number of extracurricular activities offered to the community, excelling, having quotas that have increased even beyond capacity, and starting this year, they have been given the mandate to become a driving school. Researchers used qualitative research and phenomenological approaches. The finding of the success of Al-Huda's development competitiveness is by implementing strategic management by reviewing 2 sides, namely internally and externally of the institution, with the application of TQM. The target of the quality of institutional services in the competitiveness of institutional development through two sides, namely: first, internally in the form of: a.) Quality system within the institution by implementing quality assurance; b.) Quality services between education personnel in schools; c.) Quality services between teachers and students; second, externally in the form of: a.) Quality services between schools and parents; b.) Quality service between school and community. [Penelitian ini bertujuan untuk mengetahui manajemen strategik yang digunakan dalam pengembangan di SDI Al Huda Kota Kediri. Al Huda mengalami perkembangan cukup pesat dalam 2 periode terakhir dengan menerapkan total quality management dengan dilandasi kuatnya team work bagian dari kekuatan internal untuk melakukan pembaharuan dan meningkatkan kualitas mutu layanan. Hal tersebut dibuktikan dalam penambahan beberapa kegiatan ekstrakurikuler, pencapaian prestasi, penerimaan peserta didik yang senantiasa meningkat hingga melebihi kapasitas, dan tahun 2022 diberi amanah menjadi sekolah penggerak. Penelitian ini menggunakan jenis penelitian kualitatif dan pendekatan fenomenologi. Temuan keberhasilan daya saing pengembangan Al-Huda yakni dengan menerapkan managemen strategik dengan meninjau 2 sisi, yakni secara internal dan eksternal lembaga, dengan penerapan TQM. Sasaran mutu layanan lembaga dalam daya saing pengembangan lembaga melalui dua sisi, yakni: pertama, secara internal berupa: a.) Sistem mutu dalam lembaga dengan menerapkan penjaminan mutu; b.) Layanan mutu antara tenaga kependidikan di sekolah; c.) Layanan mutu antara guru dan peserta didik; kedua, secara eksternal berupa: a.) Layanan mutu antara sekolah dan orangtua; b.) Layanan mutu antara sekolah dan masyarakat]